Cancer pain management needs and perspectives of patients from Chinese backgrounds: a systematic review of the Chinese and English literature. Issue 6 (17th January 2018) - Xu, Xiangfeng; Luckett, Tim; Wang, Alex Yueping; Lovell, Melanie; Phillips, Jane L.
Abstract: Objective: More than half of all cancer patients experience unrelieved pain. Culture can significantly affect patients' cancer pain-related beliefs and behaviors. Little is known about cultural impact on Chinese cancer patients' pain management. The objective of this review was to describe pain management experiences of cancer patients from Chinese backgrounds and to identify barriers affecting their pain management. Method: A systematic review was conducted adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were included if they reported pain management experiences of adult cancer patients from Chinese backgrounds. Five databases were searched for peer-reviewed articles published in English or Chinese journals between1990 and 2015. The quality of included studies was assessed using Joanna Briggs Institution's appraisal tools. Results: Of 3, 904 identified records, 23 articles met criteria and provided primary data from 6, 110 patients. Suboptimal analgesic use, delays in receiving treatment, reluctance to report pain, and/or poor adherence to prescribed analgesics contributed to the patients' inadequate pain control. Patient-related barriers included fatalism, desire to be good, low pain control belief, pain endurance beliefs, and negative effect beliefs. Patients and family shared barriers about fear of addiction and concerns on analgesic side effects and disease progression. Health professional–related barriers were poor communication, ineffective management of pain, and analgesic side effects. Healthcare system–related barriers included limited access to analgesics and/or after hour pain services and lack of health insurance. Significance of results: Chinese cancer patients' misconceptions regarding pain and analgesics may present as the main barriers to optimal pain relief. Findings of this review may inform health interventions to improve cancer pain management outcomes for patients from Chinese backgrounds. Future studies on patients' nonpharmacology intervention-related experiences are required to inform multidisciplinary and biopsychosocial approaches for culturally appropriate pain management.